Non-covalent interaction, adsorption characteristics and solvent effect of procainamide anti-arrhythmias drug on silver and gold loaded silica surfaces: SERS spectroscopy, density functional theory and molecular docking investigations. Issue 14 (23rd March 2023) - Vetrivelan, V.; Sakthivel, S.; Muthu, S.; Al-Saadi, Abdulaziz A.
Abstract : The structural and electronic properties of the non-covalent interaction of procainamide (PA) anti-arrhythmias drug molecules on silver-loaded and gold-loaded silica nanostructures were explored using first-principle calculations. Abstract : First-principle calculations were systematically carried out to explore the structural and electronic properties of the non-covalent interaction of procainamide (PA) anti-arrhythmias drug molecules on silver-loaded and gold-loaded silica nanostructures. Computed adsorption energies presented a higher affinity of PA towards the Ag–SiO2 as compared with Au–SiO2 surfaces. The non-covalent interaction analysis revealed a weak van der Waals type of forces and hydrogen bonding, associated with a noticeable repulsive steric interaction. It was conceived that silver and gold decorated silica can be used for drug administration in biological systems due to the fact that their frontier molecular orbital energy levels were considerably altered upon absorption, decreasing the pertinent energy gaps. Moreover, the electronic spectra of PA⋯Ag–SiO2 and PA⋯Au–SiO2 structures investigated in different solvents display a notable blue shift, suggesting that noble metal-loaded silica can be effective in the context of drug delivery systems. Therefore, silver- and gold-decorated silica of three possible drug adsorption scenarios was fully analyzed to realize the associated bioactivity and drug likeness. Theoretical findings suggest that Ag- and Au–SiO2 nanocomposites can be considered potential drug delivery platforms for procainamide in medication protocols.